Instrumen Tes untuk Mengukur Kemampuan Berpikir Kreatif Matematis dengan Bantuan Wordwall dalam Materi Eksponen Kelas XI SMAN 1 Embaloh Hulu - Sthiben, Hermanus; Muchtadi, Muchtadi; Abdillah, Abdillah (Indo-MathEdu Intellectuals Journal, 2024)
This researcher aims to develop a test instrument media to measure mathematical creative thinking skills with the help of wordwalls. The research method used is Researcd and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The level of validity, practicality, and effectiveness of the test instrument to measure mathematical creative thinking ability with the help of wordwalls on exponential material is an indicator of the feasibility of the instrument made. The data analysis used was quantitative and qualitative descriptive analysis. Media validity is obtained from the results of expert validation consisting of media experts and material experts. The results obtained from media experts with an average of 86.67% with the "very valid" criteria and the results from material experts with an average of 89.70% with the "very valid" criteria. Practicality was obtained from the percentage of student and teacher responses with an average of 86.88% with the criterion of "very practical". Effectiveness is obtained because it has met 4 criteria of effectiveness, namely the validity of question items, level of difficulty, differentiation and reliability, and can be said to be "effective". The conclusion is that the test instrument to measure mathematical thinking ability with the help of wordwalls in the exponential material of class XI SMAN 1 Embaloh Hulu is feasible to use.